P397 Response to biologics in IBD patients assessed by Computerized image analysis of Probe Based Confocal Laser Endomicroscopy with molecular labeling. (27th May 2021) - Iacucci, M; Grisan, E; Labarile, N; Nardone, O; Smith, S C; Jeffery, L; Ghosh, S; Buda, A
Abstract: Background: The increase in therapeutic choices in inflammatory bowel diseases (IBD) imposed the identification of personalized therapeutic strategy. Confocal laser endomicroscopy (CLE) is a new endoscopic tool developed to obtain virtual in vivo histology. This study aimed to identify CLE in vivo and ex vivo features predictive of response for patients starting biologics. Methods: We performed a prospective observational study at a single tertiary referral centre. 29 IBD patients (14 ulcerative colitis-UC and 15 Crohn's Disease-CD) underwent colonoscopy with CLE before and 12-14 weeks after starting anti -TNF or 16 weeks after anti α4β7 integrin. CLE parameters analyzed were: crypt distribution along the mucosal surface, crypt area (CA), eccentricity, diameter, inter-cryptic distance (ICD), vessel tortuosity (VT), fluorescein leakage through the colonic mucosa (FLCM). Ex-vivo binding activity of fluorescein labelled biologics on corresponding biopsies was also assessed. Mosaicism reconstruction of CLE images were analyzed using a dedicated software algorithm (CellvizioViewer, Mauna Kea Technologies, ParisFrance). A dedicated Graphical User Interface was designed to enable a semiautomated analysis. Results: After treatment, VT resulted significantly changed in overall IBD population (p<0.05), FLCM were reduced in UC patients (p<0.05), whilst CA, eccentricity and ICD decreased in CD patients (p< 0.05). The univariate regression analysis identified FLCM as the most accurate parameter for predicting responsiveness (AUROC) 83%, accuracy 83%, positive predictive value-PPV 94% and negative predictive value-NPV 57%). FLCM and ICD were the best discriminants in responders Vs non responders in UC patients (AUROC 85%, accuracy 85%, PPV 100% and NPV 71%); whilst VT, CA and ICD in CD patients (AUROC 95%, 86% and 83%; accuracy 90%, 90% and 88%; PPV 100%, 100% and 86%; and NPV 75%, 75% and 100%, respectively). Ex vivo confocal imaging revealed that UC patients, especially those responders, had higher basal fluorescent intensity signals with a significant reduction after biological treatment (p< 0.05), whereas in CD patients no significant change was found. An increased mucosal binding to the fluorescent labelled biological agent was associated to a higher likelihood of response to the treatment; this effect was higher in UC patients (AUROC 81%, accuracy 77%, PPV 100%, NPV 63%) compared to CD patients (AUROC 64%, accuracy 79%, PPV 80%, NPV 50%). Conclusion: FLCM and ICD were the best discriminants of response in UC, while VT, CA and ICD in CD. A higher mucosal binding to a biological agent before treatment was observed in responders UC patients but not in CD patients.